Africa and zero hunger agenda: genome editing policy landscape, challenges and opportunities - Akinbo, Olalekan; Nkhabindze, Bongani; Amedu, Josephine; Ebegba, Rufus; Asagbra, Agnes; Ratemo, Billy Omboki; Angira Dada, Susan; Muia, Anne; Mugiira, Roy; Chimphepo, Lilian; Wristberg, Leeford Oko; Rouamba, Mathurin W.; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Africa has historically struggled to adopt innovative agricultural technologies, which has significantly hindered efforts to ensure food security and improve livelihoods over the past century. A major obstacle in this regard has been the persistent skepticism surrounding the potential benefits of agricultural biotechnology. The challenges contributing to this skepticism include a notable knowledge gap among stakeholders, widespread technophobia, or fear of technology, as well as inconsistencies with global agreements such as the Convention on Biological Diversity (CBB). Although these challenges are not exclusive to Africa, they disproportionately impact the continent, making the need for effective solutions even more urgent. This paper investigates the national government policy landscape in five African countries that are poised to create a regulatory environment conducive to deploying genome editing technology for improved agricultural productivity. This exploration aligns with the continental agricultural policy initiatives, notably the “CAADP Malabo Declaration” and the soon-to-be-signed “CAADP Kampala Declaration.” Aligning with the African Union’s continental agenda on agricultural transformation, as outlined in the Malabo Declaration and other key documents, is crucial for adopting innovative agricultural technologies like genome editing. Such alignment becomes increasingly critical for realizing the objectives set forth in the post-Malabo Declaration, with the Kampala Declaration playing a vital role in its implementation. This cohesive approach will not only foster agricultural innovation but also expedite development across the continent, addressing the pressing needs of food security and livelihoods in Africa.